2018
DOI: 10.1136/bmjopen-2017-020045
|View full text |Cite
|
Sign up to set email alerts
|

Identifying priority policy issues and health system research questions associated with recovery outcomes for burns survivors in India: a qualitative inquiry

Abstract: ObjectivesThis study aimed to identify priority policy issues and health system research questions associated with recovery outcomes for burns survivors in India.DesignQualitative inquiry; data were collected through semistructured in-depth interviews and focus group discussions.SettingNine sites in urban and rural settings across India, through primary, secondary and tertiary health facilities.ParticipantsHealthcare providers, key informants, burns survivors and/or their carers.ResultsParticipants acknowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…Overall, this requires multidisciplinary efforts rather than only efforts of the health sectors. Future work in injury prevention in Vietnam may benefit from detailed quantitative and qualitative assessments, as has been done for drowning 44…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, this requires multidisciplinary efforts rather than only efforts of the health sectors. Future work in injury prevention in Vietnam may benefit from detailed quantitative and qualitative assessments, as has been done for drowning 44…”
Section: Discussionmentioning
confidence: 99%
“…Future work in injury prevention in Vietnam may benefit from detailed quantitative and qualitative assessments, as has been done for drowning. 44 …”
Section: Discussionmentioning
confidence: 99%
“…In India, also, standards are not fully complied in which provided interventions and services substantially vary from one hospital to another. Partly it is due to lack of clinical guidelines [14].…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that the lack of operating standards for burn treatment, different knowledge and skills from health professionals in providing burn care, along with resource shortages, affect the quality of burn care for patients [13]. Jagnoor et al (2017) identified the challenges of burn and recovery care such as poor communication between health care providers and burn victims, limited rehabilitation services, transportation problems to health centres, and high costs of burn treatment and confirmed the need for long-term rehabilitation [14]. Wang et al (2018) identified the challenges and improvements in burn wound healing, infection, pain and wound and explained there are challenges in long-term treatment and wound healing, infection, pain and hypertrophic wounds in burn management [15].…”
Section: Introductionmentioning
confidence: 99%
“…In general, several studies have found different community characteristics between those who live in urban and rural areas. Among them, the education status of rural communities tends to be lower than that of urban areas, opportunities to access information in rural communities are more limited, more rural communities especially women who are not working, and poverty is predominant in rural (Xu et al, 2018) (Jagnoor et al, 2018) (Weinhold and Gurtner, 2018). Other characteristics are geographical features that tend to be more severe, for example mountainous areas, uneven land contours, large forests, which have an impact on transportation difficulties, which will further strengthen the reluctance of people to go to health care facilities (Lam et al, 2018) (Jarman et al, 2018) (Spees et al, 2019).…”
Section: Introductionmentioning
confidence: 99%